1999
DOI: 10.1002/(sici)1096-9837(199905)24:5<423::aid-esp998>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Sand transport and deposition within arrays of non-erodible cylindrical elements

Abstract: The study concerns sand deposition within a regular array of vertical cylinders placed in the path of a sand-laden wind. Twelve wind tunnel experiments using three preselected shear velocities (28Á78, 32Á86 and 45Á1 cm s À1 ), with associated rates of sand feed (0Á3, 2Á0 and 3Á8 g cm À1 s À1), and four roughness element concentrations (! = 0Á046, 0Á092, 0Á184 and 0Á369) were carried out to evaluate the factors that affect sand deposition and sand flux in the presence of immobile rough elements. The measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…() (their figure 7) and the Oceano data, the element height effect on transport efficiency can be demonstrated. For λ = 0·022, the NSF and λ relationship for the Al‐Awadhi and Willetts () (average element height = 0·035 m) and Lancaster and Baas () (average element height = 0·1 m) data sets, would predict essentially no measureable effect of element height on sand transport efficiency. For the Gillies et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() (their figure 7) and the Oceano data, the element height effect on transport efficiency can be demonstrated. For λ = 0·022, the NSF and λ relationship for the Al‐Awadhi and Willetts () (average element height = 0·035 m) and Lancaster and Baas () (average element height = 0·1 m) data sets, would predict essentially no measureable effect of element height on sand transport efficiency. For the Gillies et al .…”
Section: Discussionmentioning
confidence: 99%
“…Field and wind tunnel data measurements of sand transport through roughness that is on the order of a few centimeters (Al‐Awadhi and Willetts, ) to tens of centimeters in height (e.g. Lancaster and Baas, ; Gillies et al ., ) have revealed that the reduction in sand transport scales as a power function of the roughness density ( λ ), which is defined as: λ=nbh/Swhere n is the number of elements, b the element breadth, h the element height, S the area of the surface that contains all the elements.…”
Section: Introductionmentioning
confidence: 98%
“…Validation of the model (Figure 2) has been carried out in numerous field and lab studies, as by, for example, McKenna‐Neuman and Nickling [1995], Nickling and McKenna‐Neuman [1995], Musick et al [1996], Wolfe and Nickling [1996], Grant and Nickling [1998], Sterk et al [1998], Al‐Awadhi and Willetts [1999], Crawley and Nickling [2003], and Wyatt and Nickling [1997]. While the basic form of the model has been widely adopted, its parameterization remains controversial and challenging to carry out in practice [ Crawley and Nickling , 2003], with reported measurements for m ranging from as little as 0.16 for sparse shrubs [ Wyatt and Nickling , 1997] to values possibly in excess of 1 for a developing lag surface [ Nickling and McKenna‐Neuman , 1995].…”
Section: Contextmentioning
confidence: 99%
“…Artificial plants with complicated shapes and varying flexibility were employed in this study, whereas simple stick-type plant models without flexibility were employed in previous studies (e.g., AL-AWADHI and WILLETTS, 1999;MUSICK, TRU-JILLO, and TRUMAN, 1996;TSUJIMOTO and NISHIZAWA, 1999). Simulations of Calystegia soldanella and Carex kobomugi plants, which grow on sandy beaches, were adopted as flexible vegetation models in addition to stick-type models (see Figure 2).…”
Section: Vegetation Canopiesmentioning
confidence: 99%